Mechanisms of autogenous shrinkage of alkali-activated slag and fly ash pastes. (September 2020) - Li, Zhenming; Lu, Tianshi; Liang, Xuhui; Dong, Hua; Ye, Guang
Abstract: This study aims to provide a better understanding of the autogenous shrinkage of slag and fly ash-based alkali-activated materials (AAMs) cured at ambient temperature. The main reaction products in AAMs pastes are C-A-S-H type gel and the reaction rate decreases when slag is partially replaced by fly ash. Due to the chemical shrinkage and the fine pore structure of AAMs pastes, drastic drop of internal relative humidity is observed and large pore pressure is generated. The pore pressure induces not only elastic deformation but also a large creep of the paste. Besides the pore pressure, other driving forces, like the reduction of steric-hydration force due to the consumption of ions, also cause a certain amount of shrinkage, especially in the acceleration period. Based on the mechanisms revealed, a computational model is proposed to estimate the autogenous shrinkage of AAMs. The calculated autogenous shrinkage matches well with the measured results.